2020
DOI: 10.1186/s13014-020-01546-y
|View full text |Cite
|
Sign up to set email alerts
|

Predicting per-lesion local recurrence in locally advanced non-small cell lung cancer following definitive radiation therapy using pre- and mid-treatment metabolic tumor volume

Abstract: Background We evaluated whether pre- and mid-treatment metabolic tumor volume (MTV) predicts per lesion local recurrence (LR) in patients treated with definitive radiation therapy (RT, dose≥60 Gy) for locally advanced non-small cell lung cancer (NSCLC). Methods We retrospectively reviewed records of patients with stage III NSCLC treated from 2006 to 2018 with pre- and mid-RT PET-CT. We measured the MTV of treated lesions on the pre-RT (MTVpre) and mid-RT (MTVmid) PET-CT. LR was defined per lesion as recurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…9,19,20 As response to induction therapy seems to predict long-term clinical outcomes, strategies to escalate or de-escalate treatment intensity on the basis of early response assessments may be considered.Thoracic radiotherapy is delivered using a deintensified, risk-adapted approach. Data from several institutions suggest that in-field disease progression after definitive radiotherapy for LA-NSCLC occurs almost exclusively at sites of bulky disease involvement 11,12 and modest radiotherapy doses may be sufficient to control small tumors and lymph nodes in the setting of active systemic therapy. 13 We therefore used a relatively low radiotherapy dose (48 Gy) to treat small tumors and lymph nodes in this trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,19,20 As response to induction therapy seems to predict long-term clinical outcomes, strategies to escalate or de-escalate treatment intensity on the basis of early response assessments may be considered.Thoracic radiotherapy is delivered using a deintensified, risk-adapted approach. Data from several institutions suggest that in-field disease progression after definitive radiotherapy for LA-NSCLC occurs almost exclusively at sites of bulky disease involvement 11,12 and modest radiotherapy doses may be sufficient to control small tumors and lymph nodes in the setting of active systemic therapy. 13 We therefore used a relatively low radiotherapy dose (48 Gy) to treat small tumors and lymph nodes in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…Hypermetabolic pulmonary tumors and involved lymph nodes were delineated on postinduction PET using a commercial semiautomatic contouring tool (MIMvista Corp, Cleveland, OH). 10 On the basis of patternsof-failure analyses and previous trials suggesting that small NSCLC lesions can be controlled with modest radiotherapy doses, [11][12][13] tumors and lymph nodes with the metabolic tumor volume under 20 cc received a radiotherapy dose of 48 Gy, whereas larger lesions received a dose of 55 Gy, all delivered in 20 daily fractions over 4 weeks. All patients were treated with photon radiotherapy, and standard dosimetric constraints for the brachial plexus, esophagus, heart, lungs, and spinal cord were applied.…”
Section: Study Therapymentioning
confidence: 99%
“…Previous studies showed that the MTVs of the primary tumor and regional metastatic lymph nodes displayed by 18 F-FDG PET pre-and mid-radiotherapy are significantly associated with the recurrence patterns of patients with LA-NSCLC who receive chemoradiotherapy (11). The AUC values of pre-and mid-radiotherapy MTVs for predicting LR are 0.71 and 0.76, ------------------------------------ respectively (11).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the MTVs of the primary tumor and regional metastatic lymph nodes displayed by 18 F-FDG PET pre-and mid-radiotherapy are significantly associated with the recurrence patterns of patients with LA-NSCLC who receive chemoradiotherapy (11). The AUC values of pre-and mid-radiotherapy MTVs for predicting LR are 0.71 and 0.76, ------------------------------------ respectively (11). A previous study demonstrated that patients with LA-NSCLC and a tumor volume >50 cm 3 are more prone to primary tumor recurrence after chemoradiotherapy compared with those with a tumor volume ≤50 cm 3 (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation